Emotional “Patient-Oriented” Support in Young Patients With I–II Stage Breast Cancer: Pilot Study - Di Giacomo, D.; Ranieri, J.; Donatucci, E.; Perilli, E.; Cannita, K.; Passafiume, D.; Ficorella, C. (Frontiers in Psychology, 2018)
Objective. The recent increased survival rate after breast cancer (BC) diagnosis and treatment is mostly related to early screening in younger age. Evidence gained from newly detected assessed psychological needs as well as certain emotional regulatory patterns in younger survivors has been related in the literature to an extremely low rate of adherence to the psychological therapies offered. Tailored psychological support is necessary. The aim of the present study was to verify the preliminary efficacy of supportive psychological intervention with an innovative orientation: the Early Breast Cancer Psychological Intervention (EBC-Psy). Method. A controlled study design was used to investigate the efficacy of EBC-Psy intervention. Preliminary data involved twenty-four patients in the age range of 35–50 years, diagnosed with cancer at the early stage (I–II), who were exposed to the EBC-Psy intervention. To address the effect of intervention, emotional variables were tested before the treatment (Time 1) and then again after six months of the treatment (Time 2); evaluated emotional dimensions were anxiety, anger, depression, and psychological distress. Results. EBC-Psy intervention appears to be effective on both depression (p = 0.02) and psychological distress (p = 0.01), even in a short time, highlighting the strength of a reinforced positive psychological conceptual approach to deal with the “disease condition” in younger patients; on the contrary, the control group evidenced an increase in the same emotional variables in timing. Conclusions. Our findings, even if limited by this small-scale protocol, seemed to confirm the role of positive psychotherapy after BC diagnosis and treatment through the impact of cognitive processes, coping strategies, and psychological resilience. Future theoretical framework could boost the intervention to design an innovative survivorship model.